Separation and Characterization of β-Glucanases from Penicillium ochro-chloron - Jadhav, J.P.; Dake, M.S.; Patil, N.B. (Asian Journal of Chemistry, 2010)
Two pools of glycogen exist in yeast; cytoplasmic glycogen serves as energy reservoir and cell wall bound glycogen is released on treatment with b-glucanase. Search for specific β-glucanase showed that endo(1→3)-β-D-glucanase and β-glucosidase are produced in high concentration in the cultural filtrate of Penicillium ochro-chloron. The activity of (1→3)-β-D-glucanase was inducible, when insoluble -glucans from the yeast cell wall were added in the medium (1% w/v). (1→3)-β-D-glucanase and β-glucosidase were separated by DEAE-sepharose ion exchange chromatography. Both the activities were retained by the column. Stepwise elution was achieved by using salt gradient, which resolved the retained protein into five peaks. The first peak eluted at 0.05 M NaCl concentration showed (1→3)-β-D-glucanase activity whereas the -glucosidase activity was eluted at 0.12 M NaCl concentration. The kinetic properties of (1→3)-β-D-glucanase showed that the enzyme was maximally active at temperature 60ºC, pH 5 and at 55.5 μg/mL substrate concentration when laminann was used as a substrate. Hg2+ inhibits the enzyme activity to some extent while Co2+ enhances enzyme activity. The molecular weight of (1→3)-β-D-glucanase is in the range of around 45,000 daltons. β-Glucosidase shows maximum activity at temperature between 55–60ºC, pH 5.5 and at substrate concentration 125 μg/mL when p-nitrophenyl β-D-glucopyranoside is a substrate. The molecular weight of -glucosidase is in the range around 1,13,000 daltons.